Structural Basis of Ligand Selectivity by a Bacterial Adhesin Lectin Involved in Multispecies Biofilm Formation - Shuaiqi Guo (American Society for Microbiology, 2021)
Bacterial adhesins are key virulence factors that are essential for the pathogen-host interaction and biofilm formation that cause most infections. Many of the adhesin-driven cell-cell interactions are mediated by lectins.